Gaver til klostrene i middelalderen : Den sociale og kønsmæssige fordeling af donatorer på danske herreklostre indtil 1385 - Rasmussen, Linda (Kirkehistoriske Samlinger, 1991)
The article presents and discusses the, somewhat scanty, material concerning social and sex distribution of benefactors to Danish abbeys until 1385. As was to be expected, the material - available for 8 men’s houses and 4 nunneries only - shows that an important part of the benefactions have come from royal, episcopal, and noble donors, but the peasantry is also represented. Women make up the smaller part of the donors; valued against their personal income, however, women are considered to be more sacrificing group of donors.